Macrobothriotaenia ficta (Cestoda: Proteocephalidea), a parasite of sunbeam snake (Xenopeltis unicolor): example of convergent evolution - Scholz, Tomáš; Chambrier, Alain De; Kuchta, Roman; Littlewood, D. Timothy J.; Waeschenbach, Andrea (Zootaxa, 2013)
The poorly known proteocephalidean cestode Macrobothriotaenia ficta (Meggitt, 1931) from the sunbeam snake Xenopeltis unicolor (Ophidia: Xenopeltidae) is redescribed on the basis of re-examination of its type specimens from Burma (Myanmar), and vouchers from Thailand and Vietnam. The peculiar morphology of the scolex, which is formed by four pedunculate lobe-bearing pincer-shaped suckers, is described for the first time using scanning electron microscopy. In scolex morphology, M. ficta closely resembles phyllobothriidean cestodes, parasites of elasmobranchs. However, this similarity does not reflect phylogenetic relatedness of these cestodes but instead presents an example of convergent morphological evolution of attachment organs of unrelated groups of cestodes that parasitize different groups of vertebrates. Besides scolex morphology, the genus is characterised by the possession of a very large cirrus-sac, which may reach up to the midline of proglottides, few testes (less than 60), vitelline follicles limited to the dorsal side of proglottides, a large vaginal sphincter, and eggs with a three-layered embryophore covered with rounded projections. Numerous errors in the diagnosis of M. ficta, which appeared in the literature as a result of uncritical compilation of data without examination of original material, are corrected. Multilocus phylogenetic analysis of nuclear ribosomal RNA genes ssr- and lsrDNA and mitochondrial genes rrnL and cox1 place this species among other snake-parasitizing proteocephalideans of the genus Ophiotaenia. The convergent evolution of scolex morphology across distantly related taxa is discussed.